2021
DOI: 10.24018/ejbmr.2021.6.4.978
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Organizational Culture, Leadership Style, and Work Discipline on Employee Performance

Abstract: Purpose of this study is to analyze and understand simultaneously the influence of organizational culture, management style and work discipline on the performance of employees of PT. Don't call it Timur Shakti. The original data of the questionnaire and secondary data in the data were used as probability samples. As a sampling procedure. This study is a quantitative study of seventy-line employees of PT Bintang Timur Sakti. The analytical method used in this study is to use SPSS 24 to perform multiple linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…The results of the simultaneous Test show that organizational culture and work discipline have a positive and significant effect on employee performance, in improving employee performance it is necessary to have an excellent organizational culture and work discipline (Hasibuan & Wulandari, 2017). this is in line with previous research which stated that when organizational culture and work discipline are applied and carried out with complete sense of responsibility by employees, it will have an impact on the ability employees in improving their performance (Astutik, 2016;Wahyuni & Purba, 2021;Yogaswara et al, 2015). When the organization implements an excellent organizational culture between fellow employees or between employees and superiors and company work discipline that is carried out strictly for its employees will improve employee performance, the better organizational culture will have an impact on employee performance, namely with work aggressiveness such as carrying out duties or obligations properly and correctly to provide optimal performance (Aulia et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…The results of the simultaneous Test show that organizational culture and work discipline have a positive and significant effect on employee performance, in improving employee performance it is necessary to have an excellent organizational culture and work discipline (Hasibuan & Wulandari, 2017). this is in line with previous research which stated that when organizational culture and work discipline are applied and carried out with complete sense of responsibility by employees, it will have an impact on the ability employees in improving their performance (Astutik, 2016;Wahyuni & Purba, 2021;Yogaswara et al, 2015). When the organization implements an excellent organizational culture between fellow employees or between employees and superiors and company work discipline that is carried out strictly for its employees will improve employee performance, the better organizational culture will have an impact on employee performance, namely with work aggressiveness such as carrying out duties or obligations properly and correctly to provide optimal performance (Aulia et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…A good organisational culture will certainly provide characteristics that all stakeholders in the company can be proud of. Wahyuni and Purba (2021) found that organisational culture had a significant positive effect on employee work productivity. If organisational culture is well perceived by customers/consumers, this will increase productivity.…”
Section: Effect Of Organizational Culture On Nurse Work Productivitymentioning
confidence: 99%
“…Hasil koefisien determinasi tersebut menunjukkan variabel disiplin kerja mampu menjelaskan produktivitas kerja sebesar 68,7%. Sedangkan sisanya 31,3% dipengaruhi oleh variabel lain yang tidak diteliti penelitian ini seperti motivasi kerja (Purnomo & Wahdiniwaty, 2019), lingkungan kerja (Kirana, et al, 2020), budaya organisasi (Asnora, 2020), kompensasi (Ardiansyah, et al, 2020), dan gaya kepemimpinan (Wahyuni & Purba, 2021).…”
Section: Koefisien Determinasiunclassified